2013
DOI: 10.1093/aje/kwt268
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Fine Particulate Matter, Nitrogen Dioxide, and Term Birth Weight in New York, New York

Abstract: Building on a unique exposure assessment project in New York, New York, we examined the relationship of particulate matter with aerodynamic diameter less than 2.5 μm and nitrogen dioxide with birth weight, restricting the population to term births to nonsmokers, along with other restrictions, to isolate the potential impact of air pollution on growth. We included 252,967 births in 2008-2010 identified in vital records, and we assigned exposure at the residential location by using validated models that accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 30 publications
1
44
2
2
Order By: Relevance
“…We examined the association of PM 2.5 and NO 2 with hypertensive disorders of pregnancy employing data from a unique urban air monitoring program designed to assess intra-urban variation in population exposures, and to draw on a combination of birth certificate and hospital discharge diagnoses for a large, diverse population of pregnant women across New York City. In a previous analysis of data from this study, residential concentrations of these two air pollutants were associated with a small decrement in birth weight, 23 calling for an examination of the hypothesis that this finding might be accounted for by a more marked association with hypertensive disorders.…”
Section: Introductionmentioning
confidence: 58%
“…We examined the association of PM 2.5 and NO 2 with hypertensive disorders of pregnancy employing data from a unique urban air monitoring program designed to assess intra-urban variation in population exposures, and to draw on a combination of birth certificate and hospital discharge diagnoses for a large, diverse population of pregnant women across New York City. In a previous analysis of data from this study, residential concentrations of these two air pollutants were associated with a small decrement in birth weight, 23 calling for an examination of the hypothesis that this finding might be accounted for by a more marked association with hypertensive disorders.…”
Section: Introductionmentioning
confidence: 58%
“…For example, in New York City, Savitz et al 26 found that a 10 µg/m 3 increase in PM 2.5 was associated with a 48.4 g (95% CI −62.3 to –34.5) lower birth weight. For comparison, extrapolating our results to a 10 µg/m 3 increase in PM 2.5 yields a 48.5 g (95% CI −96.6 to –0.44) difference in birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…For both monitored and modelled pollutant levels, we averaged the daily exposure estimates to determine the average levels for the entire pregnancy as well as for the first trimester (weeks 1–12), second trimester (weeks 13–26) and third trimester (weeks 27 to birth), as in previous studies 26. While our primary analyses were based on pregnancy-average pollutant levels, we additionally investigated trimester-specific exposures as vulnerability to air pollution may change over the course of pregnancy 9 14 27…”
Section: Methodsmentioning
confidence: 99%
“…Particulate matter (PM) is also commonly released into the surrounding air during tight oil and shale gas operations, especially where there are diesel emissions (66). A relationship between NO x and preterm birth has been observed (12), whereas exposure to NO x has been linked to reductions in birth weight (145,146) and IUGR (147). Ozone, another byproduct of UOG operations, has also been linked in a number of studies to LBW and preterm birth (140,144,148,149).…”
Section: Preterm Birth and Low Birth Weightmentioning
confidence: 99%